The Implementation of a Differentiated Approach in Arabic Online Interaction Skills Learning Via ChatGPT at MAN 1 Musi Banyuasin South Sumatra - Zakiyatunnisa Al Mubarokah; Urwawuska Ladini; Masykur Hamba Roohimi (Arabic Language Education Study Program, Tarbiyah and Teacher Training, UIN Prof K.H Saifuddin Zuhri Purwokerto, 2026)
This study aims to describe the implementation of a differentiated approach in learning Arabic online interaction skills through ChatGPT at MAN 1 Musi Banyuasin, South Sumatra. The research method used is descriptive qualitative with thirty-three students and one Arabic teacher as research subjects. Data collection techniques used observation, interviews, and documentation. The Miles & Huberman method of data analysis, which includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that implementing a differentiated approach in learning Arabic online interaction skills through ChatGPT consists of three stages, namely the planning, implementation and authentic assessment stages. (1) Learning planning is designed by preparing a flexible Teaching Module equipped with a mapping of student abilities and needs through diagnostic assessments. (2) Learning implementation begins with grouping students according to the mapping results to facilitate students in the learning process and discussions among their choices. (3) The authenticity of the assessment can be adjusted to the abilities and interests of students, while the diversity of assessments can be adjusted to the style and passion of students in assignments, projects or formative assessments. Meanwhile, Arabic language teachers employ a differentiated approach to content, process, and product differentiation for each student. Challenges faced by teachers in implementing the independent curriculum include curriculum adaptation, resource and time availability, and diverse student learning styles. The findings of this study indicate that the approach used by teachers in online interactive Arabic learning is effective and can facilitate student learning.